Disclosing The Implementation of Talent Management and Knowledge Management on Employee Performance at PT.XYZ - Ardhi Riyadhi; Sugeng Santoso; Erna Wijayanti; Rifqa Aqilah Zenia; Sonia Shabine Charoline (Universitas Mercu Buana, 2022)
This study describes the application of talent management and knowledge management to employee performance at PT. XYZ. The research approach is a quantitative approach through explanatory research, and a qualitative approach obtained through key informants and supporting informants in the company. The analytical tool used is multiple regression. The population is employees of PT. XYZ and the sampling technique used is the proportional random sampling technique with a questionnaire and internal company data. The study results obtained the application of talent management and knowledge management at PT. An adjusted R2 of 24.9% indicates XYZ that employee performance is influenced by talent management and knowledge management simultaneously and significantly. The partial test has no significant effect. Companies should be able to continue to improve the effectiveness of the implementation of talent management and knowledge management by overcoming these obstacles. These two variables can have a partially significant effect on employee performance.